2006
DOI: 10.3892/or.15.2.323
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of p63 has prognostic implications for patients with esophageal squamous cell carcinoma

Abstract: The p63 gene is a member of the p53 family that plays a role in cell differentiation, development and carcinogenesis. The relationship between p63 expression and the prognosis of esophageal squamous cell carcinoma (ESCC) remains unknown. The present study examines the clinical impact of p63 in patients with ESCC. Resected specimens from 180 patients with ESCC were immunostained for p63 and p53. After establishing a cut-off value for p63 expression, we statistically examined its clinical impact and relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
20
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 23 publications
4
20
0
2
Order By: Relevance
“…No, there would be no difference in the outcome with this suggested cutoff because in the present study, 96.0% of the cancers had at least 30% of their nuclei immunostained for p63 protein. These results concur with those reported by other reports [6,10,[13][14][15] . Maybe with a grading system with larger intervals and fewer grades, this could represent a change in the outcome.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…No, there would be no difference in the outcome with this suggested cutoff because in the present study, 96.0% of the cancers had at least 30% of their nuclei immunostained for p63 protein. These results concur with those reported by other reports [6,10,[13][14][15] . Maybe with a grading system with larger intervals and fewer grades, this could represent a change in the outcome.…”
Section: Discussionsupporting
confidence: 76%
“…Iwata et al [18] examined specifically the immunohistochemical expression of truncated isoforms ( ⌬ Np63) of p63 and demonstrated that there was no prognostic impact of positive expression of these isoforms in epidermoid carcinomas of the lung. On the contrary, various studies suggested that, although uncommon, the reduced expression of p63 has a negative prognostic impact [15] . Massion et al [9] reported a statistically significant association between immunohistochemical hyperexpression of p63 protein and the amplification of the TP63 gene with better survival rates, in patients with epidermoid carcinoma of the lung.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lo Muzio et al and Moergel et al also have found that the high expression of p63 is significantly associated with the poor prognosis (49,52). In contrast, some reports have shown that reduced p63 expression associates with poor prognosis in the head and neck carcinoma (53)(54)(55). Such discrepancies might be due to the monoclonal A4A antibody used in immunohistochemical analyses.…”
Section: Discussionmentioning
confidence: 60%
“…Several studies on the assessment of correlation between the positive rate of p63 and patient prognosis in head and neck carcinoma have been reported (25,49,(52)(53)(54)(55). Lo Muzio et al and Moergel et al also have found that the high expression of p63 is significantly associated with the poor prognosis (49,52).…”
Section: Discussionmentioning
confidence: 90%